Field notes contributed by Michael C. Newlon, spring 1979 - Newlon, Michael C.et al (1979)
Spring report of birds contributed by Michael C. Newlon with referred sightings from others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed